TEACHERS’ STRATEGIES AND STUDENTS’ PROBLEM IN ENGLISH SPEAKING - Hamzah, Muhammad; Nappu, Syamsiarna; Hijrah (English Language Teaching Methodology, 2023)
This study aimed to find out students' problem in English speaking and the teachers' strategies to overcome students problem in English speaking. In this study, researcher used descriptive qualitative method to describe and interprete an object in accordance with reality. Descriptive methods implemented for data analysis presented descriptively. The subjects of this study were 2 English Teachers of SMA Muhammadiyah 3 Makassar and 5 students’ of the 10 grade that were randomly chosen. The instrument used to get data was interview.The results of all data collected by interviewing the students’ problem in speaking are lack motivation, shyness, and anxiety when they speak English and the teacher strategy in english used direct method in maintain the problems and made sudents accustomed to English by always using english in class during the teaching and learning process.